1998
DOI: 10.1002/(sici)1096-9861(19981116)401:2<163::aid-cne2>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of adenosine A2A receptors in the rat central nervous system

Abstract: The A2A adenosine receptor (A2A-AR) transcript and radioligand binding sites have a distinct distribution in rat brain, restricted primarily to the striatum, nucleus accumbens and olfactory tubercles. We describe here the use of purified recombinant human A2A-ARs to generate a monoclonal antibody that has been used to better resolve the distribution of A2A-ARs in rat brain. The antibody can detect 1 ng of purified recombinant receptor by Western blotting and is potent (EC50 = 0.62 microg/ml) and highly selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 348 publications
(144 citation statements)
references
References 75 publications
10
134
0
Order By: Relevance
“…(Ferre et al, 2008) and their heterodimers also have the potential to internalise differentially from each homomers and, thereby, desensitise differentially (Hillion et al, 2002;Torvinen et al, 2005;Vidi et al, 2008). We also show here that the A 2A receptor agonist, CGS21680, did not cause any pharmacological effect on the firing rate or pattern of dopamine neurons, confirming the lack of pharmacologically accessible A 2A receptors on dopamine neurons, which is in agreement with a low level of A 2A receptor expression in the VTA (Rosin et al, 1998;Rosin et al, 2003). CGS21680 also failed to acutely alter D 2 receptor function in the VTA, indicating a lack of direct pharmacological interaction between D 2 and A 2A receptors in the VTA, like those in the striatum (Azdad et al, 2009).…”
Section: Potency Of Quinpirole On Dopamine Neuron Firing Is Similar Bsupporting
confidence: 88%
See 1 more Smart Citation
“…(Ferre et al, 2008) and their heterodimers also have the potential to internalise differentially from each homomers and, thereby, desensitise differentially (Hillion et al, 2002;Torvinen et al, 2005;Vidi et al, 2008). We also show here that the A 2A receptor agonist, CGS21680, did not cause any pharmacological effect on the firing rate or pattern of dopamine neurons, confirming the lack of pharmacologically accessible A 2A receptors on dopamine neurons, which is in agreement with a low level of A 2A receptor expression in the VTA (Rosin et al, 1998;Rosin et al, 2003). CGS21680 also failed to acutely alter D 2 receptor function in the VTA, indicating a lack of direct pharmacological interaction between D 2 and A 2A receptors in the VTA, like those in the striatum (Azdad et al, 2009).…”
Section: Potency Of Quinpirole On Dopamine Neuron Firing Is Similar Bsupporting
confidence: 88%
“…Adenosine A 2A receptors are G s/olf -coupled receptors for the endogenous neuromodulator adenosine (Fredholm et al, 2011). The expression of A 2A receptors in the brain is at the highest density in the soma of the GABAergic medium spiny neurons in the striatum, with significantly lower levels of expression elsewhere in the brain (Rosin et al, 1998;Svenningsson et al, 1999;Rosin et al, 2003). In the striatum, A 2A receptors co-localize with dopamine D 2 receptors (Ferre et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some evidence that both the dorsal and ventral striatum are directly accessed by nociceptive neurones (Newman et al, 1996) and that the ventral striatum, like many parts of the limbic system, modulates pain processing (see Millan, 1999). Using immunohistochemical techniques, most of the receptor expression is also seen in the basal ganglia (Rosin et al, 1998). However, it should be stressed that A 2A receptors are found at relatively low levels in somatosensory cortex (Johansson et al, 1997;Kelly et al, 2004) and their presence in the cortex has been confirmed by western blotting (Lopes et al, 2004), and thus a potential role of A 2A receptors in the central integration of pain cannot be completely ignored.…”
Section: Pain Circuitry and Localization Of Adenosine A 2a Receptorsmentioning
confidence: 99%
“…A 2A receptor antagonists show promising results as an adjuvant to L-DOPA therapy (see 2.3.). The dorsal striatum, which contains a high density of A 2A receptors (Rosin et al, 1998), appears to be the site of action for the antiparkinsonian effects of A 2A antagonists. The dorsal striatum receives its dopaminergic input from the substantia nigra (pars compacta), the predominant area of neurodegeneration in Parkinson's disease (Hirsch et al, 1988;Rinne, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation